Connotation, innovation and vision of “carbon neutrality” - Caineng Zou; Huaqing Xue; Bo Xiong; Guosheng Zhang; Songqi Pan; Chengye Jia; Ying Wang; Feng Ma; Qian Sun; Chunxiao Guan; Minjie Lin (Natural Gas Industry B, 2021)
Global climate change caused by geological processes is one of the main causes of the 5 global mass extinctions in geological history. Human industrialization activities have caused serious damage to the ecosystem, the greenhouse effect of atmospheric CO2 has intensified, and the living environment is facing threats and challenges. Carbon neutrality is the active action and common goal of mankind in the face of the climate change crisis, therefore, probing into its theoretical and technological connotation, scientific and technological innovation system has far-reaching significance and broad prospects. Studies indicate that (1) Carbon neutrality reflects the theoretical connotations of “energy science” and “carbon neutrality science”, including technical connotations of carbon emission reduction, zero carbon emission, negative carbon emission, and carbon trading. (2) Carbon neutrality spawns new industries such as carbon industry centering on CO2 capture, utilization, and storage (CCUS, or CO2 capture and storage CCS), and hydrogen industry centering on green hydrogen. “Gray carbon” and “black carbon” are the two application attributes of CO2. “Carbon+”, “Carbon−”, and “Carbon=” are three carbon-neutral products and technologies. (3) China faces three major challenges in achieving the goal of carbon neutrality: first, energy transition is large in scale and the cycle is short; Second, there are many problems in the process of energy transition, such as security uncertainties, economic utilization, and unpredictable disruptive technologies; Third, after transition, we may face new key techno-logical “bottlenecks” and “broken chain” of key mineral resources. (4) Based on current knowledge to predict the top 10 disruptive technologies and industries in the energy field: underground coal gasification, in-situ conversion process of medium and low-mature shale oil, CCUS/CCS, hydrogen energy and fuel cells, bio-photovoltaic power generation, space-based solar power generation, optical storage smart micro-grid, super energy storage, controllable nuclear fusion, wisdom energy Internet. Five strategic projects will be implemented, including energy conservation and efficiency improvement, carbon reduction and sequestration, scientific and technological innovation, emergency reserve and policy support. (5) In the future, different types of energy will have different orientations. Coal will play the role of ensuring the national energy strategy “reserve” and “guarantee the bottom line”. Petroleum will play the role of ensuring national energy security “urgent need” and the “cornerstone” of raw materials in people's livelihood. Natural gas will play the role in ensuring national energy “safety” and “best partner” of new energy. New energy will play the role in ensuring the “replacement” and “main force” of the national energy strategy. (6) Carbon neutrality is a major practice of the green industrial revolution, carbon reduction energy revolution, and ecological technology revolution, which will bring new and profound changes to human society, the environment and the economy. (7) Carbon neutrality needs to follow the four principles of “disruptive breakthroughs in technology, guarantee of energy security, realization of economic feasibility, and controllable social stability”. We should rely on technological innovation and management changes to ensure the realization of national energy “independence” and carbon neutrality goal, and make China's contribution to the construction of a livable earth, green development, and ecological civilization.